Triaging patients with upper gastrointestinal bleeding: the utility of Glasgow-Blatchford score - Mohanty, Namita; Kannan, Arjun Nataraj (International Journal of Research in Medical Sciences, 2019)
Background: Glasgow-Blatchford bleeding score (GBS), was developed to predict the need for hospital-based intervention (transfusion, endoscopic therapy or surgery) or death following upper gastrointestinal bleeding. Study evaluated the Glasgow Blatchford score’s (GBS) ability to identify high risk patients who needed blood transfusion in patients with UGI haemorrhage. Methods: A total of 270 cases admitted with upper gastrointestinal bleeding in the Medical ICU/Wards of MKCG Medical College were put on Blatchford scoring system and classified as those requiring (high risk = GBS >1) and not requiring blood transfusion (low risk) based on the score assigned on admission and a correlation between initial scoring and requirement of blood transfusion was done. Results: Units of blood transfusion required, the GBS and duration of hospital stay were significantly lower among the low risk group, all with p value <0.001. No blood transfusion was required in patients with GBS <3. There was significant correlation between GB score and requirement of blood transfusion (p <0.001) and duration of hospital stay (p <0.001). GBS had 100% sensitivity, negative predictive value and positive likelihood ratio, when a cut off of > 16 was used in predicting mortality. Conclusions: Patients presenting with Upper GI bleeding can be triaged in casualty with Glasgow Blatchford scoring. Patients with a low score of less than or equal to 3 can be safely discharged and reviewed on follow up thereby reducing admission, allowing more efficient use of hospital resources.